DYNAMIC EVALUATION OF CUCUMIS MELO ON NEURODEGENERATIVE MODEL OF RATS (The Research of Medical Science Review, 2025)
Objectives: Neurodegenerative disorders (NDDs) are the most concerned health issues, because of high percentage of mortality. Elderly patients mostly suffer from these diseases. Neurodegenerative disorders cause progressive damage to nervous system. Parkinson’s disease, depression, Huntington’s disease and Alzheimer’s disease are the most prevalent neurodegenerative disorders. Materials and methods: Natural products have shown significant effects in the treatment of such neuronal disorders. These natural products have improved neuronal cellular survival, growth, differentiation and activities in in-vivo/ invitro experimental models. Cucumis melo (Melon) is one of the most popular crops worldwide which belongs to the Cucurbitaceae family. Many studies were performed on different plants of this family due to their nutritional, medicinal and pharmacological values. It also shows anti-ulcer, analgesic, anti-inflammatory, anti-diabetic and diuretic activities. This study is based on evaluating the neuronal activities of natural seed extracts of Cucumis melo in in-vivo/ invitro experimental models. The ethanolic extracts of Cucumis melo seeds was investigated for evaluating the neuronal effects in Wistar albino rats and albino mice. Experiments were performed to analyze the effects of the extracts on genetic marker (IL-6) involved in neuromodulation. In-vitro neuronal activity was carried out through anti-oxidant scavenging activity method, cell viability test, anti-microbial activity and anti-inflammatory activity and ELISA on neonatal hippocampal cells. Results were calculated by means of ANOVA (One way, Tukey’s - Post hoc test) Results: Results of the study have demonstrated the extract have shown significant reduction in neurodegeneration and neuroinflammation. It has also provided significant reduction in in-vitro free radical scavenging activity and enhanced neuronal cell proliferation. Conclusion: This study suggested that the extract had shown an important consideration about the pharmacological effects of Cucumis melo as an alternative therapy to conventional drugs for treatment of neurological disorders.